Modelling the Effect of Perforations on In-Package Environment of Stored Mangoes - Kumar, Satish; Gupta, A K (Journal of Agricultural Engineering, 2005)
Studies were carried out to develop a suitable mathematical relationship between level of perforations, O2 and CO2 concentrations and levels of relative humidity inside the package. The experiments were carried out to verify the model results. The gaseous and water vapour transmission rates of the polymeric films were found experimentally. The CO2 transmission rate of LDPE-80 film was found to be much higher than 02. Perforations resulted in more transmission of O2 than CO2, Exchange of gases through perforations accounted for 97-98 per cent while film had 2-3 per cent of total gas exchange. Perforations resulted in considerable reduction in the time period to attain steady state levels of O2 while the effect was not as much on the time period to attain the steady state of CO2 gas. The increase in number of perforations and decrease in ambient RH resulted in only a little decrease in RH within the package but it remained above 95 per cent. A perforation area of around 2.7x10-3 percent would give optimum levels of O2 ~ 6 percent and CO2 ~ 9 percent to prevent the development of off flavours in the packaged mangoes (Dashahri).